PENINGKATAN PENGETAHUAN CLINICAL INSTRUKTUR (CI) TENTANG PATIENT SAFETY DI RSUD KARAWANG - Suryani, Lilis (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Clinical supervisors or Clinical Instructure (CI) are critical to the educational process of students who perform clinical work in hospitals. Nursing students practicing in hospitals may potentially make errors, such as incorrectly administering injectable medicines, resulting in patient losses. Students committed this error when they were not accompanied by a clinical supervisor. From all of the issues that exist in the guidance process activities performed by clinical supervisors at Partners, it has been determined that the following aspects are priorities for improving the quality of Partners clinical supervisors, such as: increased understanding of the role of clinical supervisors, patient safety, implementation in the guidance process for students practicing in hospitals, as well as management understanding. The purpose of this Community Service (PKM) is to increase clinical supervisors' knowledge and role in patient safety at the Karawang Regional General Hospital (RSUD) through training. The model used to deliver this training is a participatory approach that is conducted online due to the fact that it is still in a pandemic condition. Through this training, hospital clinical supervisors' knowledge is increased, which has a good effect on student actions regarding patient safety.